1980
DOI: 10.1016/0049-3848(80)90249-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrical induction of coronary artery thrombosis in the ambulatory canine: A model for evaluation of anti-thrombotic agents

Abstract: A simple technique for the reliable induction of coronary artery thrombosis in a conscious dog by delivery of low amperage electric current to the intimal surface of the artery io described. Ibuprofen, an agent known to inhibit platelet function and ptostaglandin synthesis is evaluated in this model. Comparison of myocardial infarct site, throabur weight, arrhythmia development and scanning electron nicrographs of drug treated and control animals indicate that Ibuprofen is capable of protecting against the del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 5 publications
2
82
0
Order By: Relevance
“…We used an experimental model in which thrombosis was induced by electrical stimulation applied to the intimal surface of the left circumflex coronary artery (LCCA) at the point of an external stenosis. 13 We found that administration of the 7E3 F(ab')2 after rt-PA-induced thrombolysis not only prevented thrombotic coronary artery reocclusion but also stabilized coronary artery blood flow in the recanalized vessel and was associated with an overall reduction in infarct size. Despite inhibition of platelet-fibrinogen interactions and rethrombosis, restoration of coronary artery blood flow at a level similar to baseline was not maintained.…”
mentioning
confidence: 72%
“…We used an experimental model in which thrombosis was induced by electrical stimulation applied to the intimal surface of the left circumflex coronary artery (LCCA) at the point of an external stenosis. 13 We found that administration of the 7E3 F(ab')2 after rt-PA-induced thrombolysis not only prevented thrombotic coronary artery reocclusion but also stabilized coronary artery blood flow in the recanalized vessel and was associated with an overall reduction in infarct size. Despite inhibition of platelet-fibrinogen interactions and rethrombosis, restoration of coronary artery blood flow at a level similar to baseline was not maintained.…”
mentioning
confidence: 72%
“…Platelet aggregation to collagen and the endoperoxide/thromboxane A2 mimetic U46619, as well as to ADP, was also assessed in some experiments before and after administration of bitistatin. Platelet aggregation to collagen and U46619, as well as ADP, was blocked by bitistatin at a bolus dose of 30 ,u/kg i.v. followed by an infusion of 3 ,ug/kg/min ( Figure 5).…”
Section: Discussionmentioning
confidence: 93%
“…26 The experimental procedure results in the formation of a platelet-rich intravascular thrombus at the site of an electrolytically induced endothelial lesion in proximity to a distal arterial stenosis. Use of both carotid arteries made it possible to examine dose-response relations as well as the effects of time on efficacy of the interventions.…”
Section: Model Of Carotid Occlusionmentioning
confidence: 99%